Damned life is short, death is forever - Palahniuk, Chuck (New York Doubleday, 2011)
As thirteen-year-old Madison tries to figure out how she died and ended up in Hell, she learns how to manipulate the corrupt system of demons and bodily fluids.
Sequel: Doomed.
Keywords: Hell -- Fiction; Future life -- Fiction; Dead -- Fiction